Servant leadership as employee-organization approach for performance of employee citizenship behaviors in the Nigeria’s electric power sector - Abdu Ja'afaru, Bambale; Mohd Shamsudin, Faridahwati; Chandrakantan, Subramaniam (International Journal of Global Business (IJGB), 2012)
This study is a conceptual paper that will investigate the possible significant effect of servant leadership behaviors on the employee organizational citizenship behaviors (OCBs).Organizational citizenship behaviors are job behaviors which are voluntary, not formally or directly recognized by the organizational reward system, but promote the effectiveness of the organization.Because of its positive relationship with organizational effectiveness, this study is concerned with encouraging its performance among employees of the Nigeria's power sector.The study will specifically be conducted in the Distribution Company (Disco) of the Power Holding Company of Nigeria (PHCN) Plc that is currently experiencing a major reform.The reform program is geared to provide access to private investment, efficient and effective operations of the Nigeria's electric power sector.Efficient and effective operations of the Nigeria's electric power sector are essential for growth and development of all sectors of the Nigeria's economy.